Aplikasi Geometri Euclid dalam Kehidupan Sehari-hari : Daru Arsitektur hingga Navigasi - cindy, silvia (Faculty of Arts and Education, 2023)
The principles of Euclidean geometry, established by the ancient Greek mathematician Euclid, still play an important role in many areas of daily life. This article explores various applications of Euclidean geometry, from architectural design to navigation systems and more. In architecture, Euclidean geometry provides the basic principles for building stable and aesthetically pleasing structures, ensuring that buildings are functionally and visually harmonious.Architects and engineers use these principles to create designs that are not only structurally sound, but also space and material efficient. In the field of navigation, Euclidean geometry helps map locations and calculate distances accurately, facilitating efficient travel and transportation.For example, GPS technology uses these geometric principles to provide precise directions, optimize routes, and make travel more comfortable and safe.Additionally, Euclidean geometry is an important part of many everyday tasks and technologies, such as computer graphics, engineering, and robotics. Computer graphics uses the principles of Euclidean geometry to create realistic animations and simulations that enhance the visual experience of video games and movies.In engineering, these principles are important for designing machines and infrastructure that meet precise specifications and safety standards.In robotics, Euclidean geometry helps develop algorithms that allow robots to navigate and interact effectively with their environment. Keywords: Navigation, Graphics, Architecture, Materials, Structural